Psychological distress and its impact on glycemic control in patients with diabetes, Northwest Ethiopia - Sendekie, Ashenafi Kibret; Limenh, Liknaw Workie; Bizuneh, Gizachew Kassahun; Kasahun, Asmamaw Emagn; Wondm, Samuel Agegnew; Tamene, Fasil Bayafers; Dagnew, Ephrem Mebratu; Gete, Kalab Yigermal; Kassaw, Abebe Tarekegn; Dagnaw, Abera Dessie; Tadesse, Yabibal Berie; Abate, Biruk Beletew (Frontiers in Medicine, 2025)
BackgroundDiabetes distress is the emotional and mental burden of living with diabetes. It can include feelings of frustration, guilt, anxiety, and worry. Understanding the factors contributing to psychological distress and how it affects glycemic control can be crucial for improving patient outcomes. Therefore, this study investigated the association between psychological distress levels and glycemic control in patients with diabetes. It also identified factors associated with severity of psychological distress.MethodsA multicentre cross-sectional study was conducted among patients with diabetes at selected hospitals in Northwest Ethiopia. Psychological risk distress was measured using the Kessler 10 (K10) questionnaire, validated for this population. Glycemic control was categorized as poor and good based on patients’ current glucose records and following recommended guidelines. Logistic regression examined the association between psychological distress levels and glycemic control. Linear regression assessed the association between psychological distress score and other independent variables. p-value <0.05 was considered statistically significant.ResultsMore than half (218, 54.2%) of the participants had severe psychological distress with a 27.4 (±4.6) mean score. Patients with moderate [AOR = 1. 85, 95% CI: 1.05–3.76] and severe [AOR = 2.84, 95% CI: 1.32–7.31] distress levels significantly had poor glycemic control compared to those with no distress. BMI [β = 0.61, 95% CI: 0.42, 71], monthly salary [β = −0.41, 95% CI: −67, −0.25], source of healthcare cost [β = −0.75, 95% CI: −2.36, −0.03], SMBG practicing [β = −0.85, 95% CI: −1.93, −0.25], lifestyle modifications [β = −1.66, 95% CI: −3.21, −0.18], number of medical conditions [β = 0.72, 95% CI: 0.57, 2.81], number of medications [β = 2.26, 95% CI: 1.05, 4.57], hypoglycaemia perception [β = 2.91, 95% CI: 1.32, 7.01], and comorbidity and/or complications [β = 3.93, 95% CI: 1.08, 6.72] were significantly associated with severity of psychological distress.ConclusionMost patients reported having moderate to severe psychological distress, which in turn, negatively impacted their glycemic control. Interventions incorporating mental health and psychosocial support should be implemented to relieve psychological distress and improve glycemic control.